2022
DOI: 10.1128/jmbe.00326-21
|View full text |Cite
|
Sign up to set email alerts
|

Twitter: More than Tweets for Undergraduate Student Researchers

Abstract: During the COVID-19 pandemic, biology educators were forced to think of ways to communicate with their students, engaging them in science and with the scientific community. For educators using course-based undergraduate research experiences (CUREs), the challenge to have students perform real science, analyze their work, and present their results to a larger scientific audience was difficult as the world moved online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This is also parallel with the findings of previous study that showed Twitter can improve the spread of information to the students which was conducted on a different topic (Al-Khalifa et al, 2022). Another benefit of using Twitter is the ability to share messages with other users or followers (Reyna et al, 2022), which in this case, refer to the students. This feature allows lecturers to send messages direct and on-point within the words limit.…”
Section: Using Twitter To Decimate Information Outside Of the Classroomsupporting
confidence: 86%
“…This is also parallel with the findings of previous study that showed Twitter can improve the spread of information to the students which was conducted on a different topic (Al-Khalifa et al, 2022). Another benefit of using Twitter is the ability to share messages with other users or followers (Reyna et al, 2022), which in this case, refer to the students. This feature allows lecturers to send messages direct and on-point within the words limit.…”
Section: Using Twitter To Decimate Information Outside Of the Classroomsupporting
confidence: 86%
“…Moreover, we did not attempt to separate different types of Twitter use, e.g. for expression opinions and debates versus more structured activities, such as education [16]. We also made no effort to judge the veracity, tone, sentiment and constructiveness (or lack thereof) of the tweets [17], since this is extremely difficult to do for people covering such a wide range of expertise.…”
Section: Discussionmentioning
confidence: 99%
“…These fragments of information have grown into informational treasure troves, providing numerous opportunities for analyzing consumer behavior, which is particularly useful in predicting product sales [2], stock market trends [3], and election results [4]. More than 300 million active users use X, which is one of the most widely used microblogging services [5], [6]. Due to its importance in understanding user's feelings and insolences, X Sentiment Analysis has received a lot of attention [7][8][9].…”
Section: Introductionmentioning
confidence: 99%